Report of the Co-operative Planning Committee Appointed by the Government of India on the Recommendation of the Fourteenth Registrars' Conference. Bombay 1946 - Ministry of Food and Agriculture (Ministry of Food and Agriculture, 1946)
The 1946 Report of the Co-operative Planning Committee outlines a comprehensive strategy for strengthening India’s co-operative movement to enhance rural economic development, agricultural productivity, and social welfare. It emphasizes the role of co-operatives in pooling resources, improving access to credit, promoting mechanization, and facilitating marketing of agricultural produce. Key recommendations include establishing agricultural and consumer co-operatives, milk unions, crop and livestock insurance schemes, and linking credit with production and marketing. The report advocates education and training programs for cooperative members, de-officialization to encourage local governance, and legislative reforms to streamline operations. Overall, the report envisions a structured, multi-sectoral cooperative framework that empowers rural communities, supports economic stability, and integrates cooperative principles across agriculture, urban consumer services, and financial systems.
Ministry of Food and Agriculture
Keywords: Co-operative Societies; Agricultural Credit; Rural Development; Milk Production; Crop Insurance; Cooperative Financing; Education and Training; Urban Co-operatives; Economic Planning; Livestock Insurance